Breaking Bad : A Disaggregated Analysis of Inflation Inertia - Cevik, Serhan (IMF Working Papers; Working Paper, 2022)
The post-pandemic rise in consumer prices across the world has renewed interest in inflation dynamics after decades of global disinflation. This paper contributes to the literature by providing a granular investigation of inflation persistence at the city level in Lithuania during the period 2000-2021, as well as a comparison of inflation persistence at the country level vis-a vis the eurozone over the same period. Using disaggregate monthly data collected in five major cities, the empirical analysis finds a mixed and ambiguous picture of inflation persistence. While the headline inflation does not appear to exhibit a high degree of persistence, most consumption categories have significant persistence. As a result, shocks may not remain transitory and instead have persistent effects that could spillover across subcomponents depending on the size of the shock.